Down syndrome and parental depression: A double hit on early expressive language development. (May 2020) - D'Souza, Hana; Lathan, Amanda; Karmiloff-Smith, Annette; Mareschal, Denis
Highlights: Parental depression relates to slower rate of expressive language development in young children with Down syndrome. No association with parental depression was found for any other domain. Parental depression and Down syndrome may constitute a double hit on expressive language development. Abstract: Background and aims: Down syndrome (DS) is often characterised by intellectual disability with particular difficulties in expressive language. However, large individual differences exist in expressive language across development in DS. In the general population, one of the factors associated with variability in this domain is parental depression. We investigated whether this is also the case in young children with DS. Methods: Thirty-eight children with DS between 8 and 48 months of age participated in this study. Their parents reported on the children's receptive and expressive vocabularies (MacArthur-Bates Communicative Development Inventory) and on parental depression. Furthermore, an experimenter-led standardized developmental assessment (Mullen Scales of Early Learning) was administered to the children to test five domains: gross motor, fine motor, visual reception, receptive language, and expressive language. Results: A cross-sectional developmental trajectories analysis demonstrated that expressive language developed at a slower rate in children with DS whose parent reported depression than in those whose parent did not. No differences between groups were found in any other domain. Conclusion: Parental depression is associated with slower rate of expressive language development in young children with DS. These findings suggest that DS and parental depression may constitute a double hit leading to increased difficulties in the development of expressive language.